2020
DOI: 10.2463/mrms.mp.2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of B<sub>1</sub><sup>+</sup>-corrected FISP-based Magnetic Resonance Fingerprinting: Accuracy, Repeatability and Reproducibility of T<sub>1</sub> and T<sub>2</sub> Relaxation Times for ISMRM/NIST System Phantom and Volunteers

Abstract: Purpose: This study aimed to evaluate comprehensively; accuracy, repeatability and reproducibility of T 1 and T 2 relaxation times measured by magnetic resonance fingerprinting using B + 1 -corrected fast imaging with steady-state precession (FISP-MRF). Methods:The International Society of Magnetic Resonance in Medicine/National Institute of Standards and Technology (ISMRM/NIST) phantom was scanned for 100 days, and six healthy volunteers for 5 days using a FISP-MRF prototype sequence. Accuracy was evaluated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
(75 reference statements)
8
21
2
Order By: Relevance
“…36,52 By incorporating B 1 + -correction in FISP based MRF, Kato et al reported a CV of <1% for T 1 and <3% for T 2 in selected vials of ISMRM/NIST phantom. 53 A noticeably reduced CV of <3% was reported for a range of T 2 values in the above study compared to the previously reported value of <7% without B 1 correction. 46 A controlled study using a B 1 corrected MRF method could examine the temperature dependence of estimated T 1 and T 2 values.…”
Section: Discussioncontrasting
confidence: 51%
“…36,52 By incorporating B 1 + -correction in FISP based MRF, Kato et al reported a CV of <1% for T 1 and <3% for T 2 in selected vials of ISMRM/NIST phantom. 53 A noticeably reduced CV of <3% was reported for a range of T 2 values in the above study compared to the previously reported value of <7% without B 1 correction. 46 A controlled study using a B 1 corrected MRF method could examine the temperature dependence of estimated T 1 and T 2 values.…”
Section: Discussioncontrasting
confidence: 51%
“…Kato et al 148 investigated FISP-based MRF with B 1 + correction and T1 and T2 measurements on the ISMRM/NIST phantom scanned for 100 days and showed high repeatability with a CV of T1 less than 1% and that of T2 less than 3%, which were better than the values reported by Jiang et al 149 without B 1 + correction. Korzdorfer et al 150 investigated the repeatability and reproducibility of T1 and T2 measurements by FISP-based MRF with B 1 + correction on the brains of 10 healthy volunteers, each of which were scanned 4 times using 4 or more of the 10 MRI scanners; these include 3 different models at 3 T from the same vendor at 4 sites.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 89%
“…9 MRF can also be used to evaluate the changes of T 1 and T 2 in brain parenchyma. [10][11][12][13] There is an advantage in that the dynamic range is larger using MRF than for 3D-real IR imaging alone.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this study was to evaluate the feasibility of detecting slight contrast effects in CSF and brain parenchyma after intravenous administration of single dose GBCA (IV-SD-GBCA). For this purpose, we used both 3D-real IR imaging 3 , 8 , 9 , 14 and MRF 9 , 10 , 30 pre- and post-intravenous injection of GBCA through 24 h to evaluate the contrast in the CSF, cochlear perilymphatic space, and in the cerebellar white and gray matter. This study represents a next step for research of the glymphatic system in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%